Evaluating the impact of urban landscape elements on the sense of security and local belonging-case study: Tongdejie, China - Zhu, Yue; Du, Ruichao (Frontiers in Environmental Science, 2024)
Introduction: The urban landscape is a pivotal element shaping the urban space and significantly influences its desirability or undesirability. It has a profound connection with people and their living environment, playing a crucial role in providing identity and a sense of peace to citizens. As urbanization expands and population density increases, the importance of security as a basic need within the urban structure becomes even more significant. A confusing, unattractive, or monotonous urban space can adversely affect citizens’ feelings and reduce their sense of security. Methods: In this research, we investigated the relationship between urban landscape components and the sense of local belonging, as well as the relationship between the sense of security and the urban landscape. We sought to understand how the design and planning of the urban landscape can have a positive impact on urban life and increase citizens’ sense of belonging to the city and its surroundings. Results: Our findings revealed a positive and significant correlation between the sense of local belonging and the sense of security. Living in a safe, attractive, and desirable environment fosters and strengthens feelings of belonging to the environment. This strengthening of the sense of belonging increases residents’ satisfaction and enhances the quality of life in cities. Discussion: The urban landscape serves as a powerful tool that, when optimally designed, can positively influence urban life and enhance citizens’ sense of belonging to their city and its surrounding environment. By prioritizing security and creating aesthetically pleasing and engaging urban spaces, cities can significantly improve the well-being and quality of life of their residents.